2020
DOI: 10.3389/fpubh.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Battle Against Musculoskeletal Tumors: Descriptive Data of Military Hospital Experience

Abstract: Background: Management of musculoskeletal tumors remains challenging for orthopedic surgeons. The aim of this cross-sectional study was to present the prevalence and localization of musculoskeletal disorders diagnosed and treated at a tertiary referral military hospital. Method: A total of 552 patients' medical records who presented to our clinic between 2009 and 2014 with the diagnosis of musculoskeletal tumors were retrospectively analyzed according to age, gender, bone/soft tissue localization, histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Data statistical results showed the crowd of cartilantic tumors in the middle of the 40-year-old population changes with age, and the chance of chondrosarcoma will also change [1]. Primary malignant bone tumors mainly occur in long bones of the limbs, which increases the di culty of imaging diagnosis due to various types of tumors [2]. Iliac bone lesions are more common, such as at bones with abundant red bone marrow, and myeloma and metastatic tumors are also more common.…”
Section: Introductionmentioning
confidence: 99%
“…Data statistical results showed the crowd of cartilantic tumors in the middle of the 40-year-old population changes with age, and the chance of chondrosarcoma will also change [1]. Primary malignant bone tumors mainly occur in long bones of the limbs, which increases the di culty of imaging diagnosis due to various types of tumors [2]. Iliac bone lesions are more common, such as at bones with abundant red bone marrow, and myeloma and metastatic tumors are also more common.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In another study in a military hospital in Turkey, similar comparative findings were found by Neyisci et al on 317 bone localized tumors. [14] Another regional comparative study from Iran by Solooki et al, 426 pathologic reports from 1997 to 2008 were reviewed. The findings were as follows: the commonest malignant bone tumors were osteosarcoma, metastasis, Ewing's sarcoma, and chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%